Cracking the ANP32 whips: Important functions, unequal requirement, and hints at disease implications. (25th August 2014) - Reilly, Patrick T.; Yu, Yun; Hamiche, Ali; Wang, Lishun
<x xml:space="preserve">Abstract</x> The acidic (leucine‐rich) nuclear phosphoprotein 32 kDa (ANP32) family is composed of small, evolutionarily conserved proteins characterized by an N‐terminal leucine‐rich repeat domain and a C‐terminal low‐complexity acidic region. The mammalian family members (ANP32A, ANP32B, and ANP32E) are ascribed physiologically diverse functions including chromatin modification and remodelling, apoptotic caspase modulation, protein phosphatase inhibition, as well as regulation of intracellular transport. In addition to reviewing the widespread literature on the topic, we present a concept of the ANP32s as having a whip‐like structure. We also present hypotheses that ANP32C and other intronless sequences should not currently be considered bona fide family members, that their disparate necessity in development may be due to compensatory mechanisms, that their contrasting roles in cancer are likely context‐dependent, along with an underlying hypothesis that ANP32s represent an important node of physiological regulation by virtue of their diverse biochemical activities.